Adaptive odd impulsive consensus of multi-agent systems via comparison system method. (February 2020) - Ma, Tiedong; Yu, Tiantian; Huang, Jiangshuai; Yang, Xinsong; Gu, Zhenyu
Abstract: This paper investigates the adaptive consensus problem of multi-agent nonlinear systems with odd impulsive control sequence. Based on the theory of impulsive differential system and Lyapunov stability, some new comparison system method-based sufficient criteria are derived to achieve the consensus of multi-agent nonlinear systems with uncertain parameters. Different from the existing methods of fixed impulsive consensus of multi-agent systems, the proposed impulsive control protocol with odd impulse sequence is more effective and flexible in real systems. Finally, the simulation is given to illustrate the effectiveness and validity of the theoretical results.